The INVOLVEMENT OF HLA-DRB1*11 AND HLA-DRB1*12 ALLELES IN THE OCCURRENCE OF DENGUE FEVER IN BURKINA FASO - Lassina TRAORE; Olawoumi Fabrice KOUTA; Aziz Sidi Aristide TAPSOBA; Abdoul Karim OUATTARA; Richard KANFON; Maïmounatou Rufaïda YOUGBARE; Fadilatou TASSEMBEDO; Mousso SAVADOGO; Nafissatou SANON; Shoukrat Ohuwa Toyin BELLO; Bagora BAYALA; Amana METUOR DABIRE; et al. (Journal of Experimental and Molecular Biology)
Introduction: Dengue has become the world's most common arbovirosis. In some individuals, genetic factors can increase the risk of developing severe dengue fever. Human leukocyte antigen (HLA) genes are one of the most extensively studied gene groups in human disease. The present study investigated HLA DRB1*11 and HLA DRB1*12 polymorphisms in dengue cases and their susceptibilities in the development of dengue in a population in Ouagadougou, Burkina Faso.